Flow and heat transfer characteristics of air in square channel heat exchanger with c-shaped baffle: A numerical study - Boonloi, Amnart; Jedsadaratanachai, Withada (My University, 2019)
The purpose of the present work is to study flow configuration and heat transfer behavior in a square channel heat exchanger equipped with C-shaped baffle. The influences of flow attack angle and baffle size on flow and heat transfer characteristics are considered for the laminar flow regime with the Reynolds number around 100 – 2000. The numerical study with finite volume method is selected for the present investigation. The SIMPLE algorithms is opted to solve the numerical problem. The numerical results are concluded in terms of flow and heat transfer mechanisms in the tested section. The thermal performance analysis; Nusselt number ratio (Nu/Nu0), friction factor (f/f0) and thermal enhancement factor (TEF), are also summarized. The numerical model of the smooth square channel is validated with the correlations on both Nusselt number and friction factor. The numbers of grid cell for the computational domain are also compared. The numerical results reveal that the C-shaped baffle in the tested section leads to the appearance of the thermal boundary layer disturbance on the channel walls that the important cause for heat transfer rate and thermal efficiency enhancements. The maximum TEF of the square duct with C-shaped baffle is around 3.89. In addition, the optimum gap spacing value for the square channel inserted with C-shaped baffle is around 5%.
Keywords: C-shaped baffle; Heat transfer; Numerical study; Nusselt number; Thermal performance